2007
DOI: 10.1001/archopht.125.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Modified Early Treatment Diabetic Retinopathy Study and Mild Macular Grid Laser Photocoagulation Strategies for Diabetic Macular Edema

Abstract: Purpose-To compare two laser photocoagulation techniques for treatment of diabetic macular edema (DME): modified-ETDRS direct/grid photocoagulation (mETDRS) and a, potentially milder, but potentially more extensive, mild macular grid (MMG) laser technique in which small mild burns are placed throughout the macula, whether or not edema is present, and microaneurysms are not treated directly.Methods-263 subjects (mean age 59 years) with previously untreated DME were randomly assigned to receive laser photocoagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(56 citation statements)
references
References 21 publications
1
55
0
Order By: Relevance
“…Laser therapy was performed according to a modified ETDRS protocol [20]. The eyes were examined every month after focal/grid lasering.…”
Section: Methodsmentioning
confidence: 99%
“…Laser therapy was performed according to a modified ETDRS protocol [20]. The eyes were examined every month after focal/grid lasering.…”
Section: Methodsmentioning
confidence: 99%
“…One eye of each patient which was perfectly matched for both preoperative BCVA and OCT-based CMT (Stratus™) values was selected, if she/he had both eyes eligible for the study. Group 1 eyes were treated with GL photocoagulation (modified ETDRS protocol) [6], group 2 with 1.25 mg IVB (0.05 ml; Altuzan®) injection, and group 3 with 4.0 mg/0.1 ml IVTA (Kenacort™) injection. Patients who had CMT values of less than 300 µm, and associated ocular and/or systemic conditions affecting visual outcome including those who had undergone cataract surgery and panretinal photocoagulation within the previous 6 months, amblyopia, glaucoma and vitreoretinal surgery at any time, vitreomacular traction, vitreoretinal interface abnormalities including epiretinal membrane, and ischemic maculopathy; hypertension, increased glycosylated hemoglobin (8%), diabetic nephropathy and pregnancy at any time, were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…A summary of past and ongoing DRCR network trials can be found in Table 1. The early trials within the DRCR network helped evaluate techniques of laser for the treatment of diabetic macular edema (DME)[1] and helped define the natural history of progression of DME as observed using the newly available tools of OCT.[16,17] Special interest in the utilization of triamcinolone for the treatment of DME was investigated with protocol B and the clinical efficacy of this steroid for DME was found to be inferior to macular laser. [2] The focus of the DRCR network was then turned to the use of anti-VEGF agents and the network’s first trial evaluating bevacizumab for DME was published in 2007.…”
Section: Drcr Network History-targeting Vision Loss From Diabetic Retmentioning
confidence: 99%